Threats to Poland’s Economic Security in Connection with China’s Belt and Road Initiative (Chinese: Yi dai yi lu) in 2015–2023 (Economic and Political Thought, 2023)
The article assesses the threats caused by the Chinese Belt and Road Initiative(BRI) for Poland’s economic security in 2015–2023. A literature reviewon the Belt and Road Initiative (BRI) was used, as well as an analysis of availabledata, expert knowledge resulting from investment projects completedin Poland under IPS, the author’s previous publications on this topic, andthe author’s professional experience in projects in one of the Chinese companies—technology in the Central and Eastern European region. The articleaims to answer the question of whether the Chinese Belt and Road initiativethreatens Poland’s economic security. The added value of the article is theanalysis of the impact of the Belt and Road Initiative on Poland’s economicdevelopment as part of changes in the functioning of the European Union.The author refers to Modliński’s theory of hegemonic cycles to answer thequestion and also discusses the possibilities of alternative solutions to theChinese Belt and Road Initiative. The research gap is the issue of assessingthe threat to Poland’s economic security in connection with the implementedBRI initiative.
Keywords: Belt and Road Initiative (BRI), economic security, Modlinski cycles, geoeconomics, Index FirePower (IFP), RCEP, CAI, IMEC